Maxillary Premolars with Four Canals: Case Series - Calogero Bugea; Denise Irene Karin Pontoriero; Gaia Rosenberg; Giacomo Mario Gerardo Suardi; Gianmarco Calabria; Eugenio Pedullà; Giusy Rita Maria La Rosa; Francesco Sforza; Antonio Scarano; Roberto Luongo; Giovanni Messina (Bioengineering, 2022)
The aim of this case series is to contribute to the better knowledge and management of the complex anatomical configurations of maxillary premolars with four canals. The paper explains the endodontic treatment of five maxillary premolars with four canals, with three buccal and one palatal orifices, in different patients. The cases report several approaches in the treatment of four-canal maxillary premolars including a conservative canal preparation with a hybrid shaping technique, endodontic microsurgery and the application of biomaterials. The use of an operating dental microscope, different operating strategies and the critical evaluation of radiographs are all necessary steps for the correct and safe endodontic management of these teeth.